Perbedaan Skor Domain Health Promoting Lifestyle Antar Kategori Persentase Lemak Tubuh - Ahmad Rizki Akbar Dwiputra; Rizki Suganda Prawiradilaga; Samsudin Surialaga (Bandung Conference Series: Medical Science, 2024)
Abstract. Body fat percentage (%BF) is a primary concern in the context of health and lifestyle. Excessive body fat can lead to serious health issues and contribute to the risk of chronic diseases, while the pressure to achieve an 'ideal' body can negatively impact an individual's psychological aspects. This study aims to observe differences in the health promoting lifestyle profile-2 (HPLP-II) domains across %BF categories among students of the Faculty of Medicine. This research employed an observational analytic quantitative method with a cross-sectional approach. The study involved 96 active medical faculty students willing to measure their %BF and complete the questionnaire as inclusion criteria. Exclusion criteria included incomplete questionnaire responses and a history of congenital diseases. Sampling was done using purposive sampling technique. Body fat percentage was measured using bioimpedance analysis and categorized into low, normal, overweight, and obesity. The health-promoting lifestyle profile domains were assessed using the HPLP-II questionnaire, which includes Health Responsibility (HR), Physical Activity (PA), Nutrition (N), Spiritual Growth (SG), Interpersonal Relationship (IR), and Stress Management (SM) domains. The results were analyzed using one-way ANOVA. The study found no significant differences across %BF categories in all HPLP domains: HR (p=0.964), PA (p=0.532), N (p=0.616), SG (p=0.547), IR (p=0.547), and SM (p=0.376). The lack of significant differences in this study may be due to other factors influencing %BF, such as genetics, metabolism, and culture. Abstrak. Persentase lemak tubuh (%LT) menjadi perhatian utama dalam konteks kesehatan dan gaya hidup. Lemak tubuh yang berlebihan dapat menyebabkan masalah kesehatan serius dan berkontribusi pada risiko penyakit kronis, sementara tekanan untuk mencapai tubuh "ideal" dapat berdampak negatif pada aspek psikologis individu. Penelitian ini bertujuan untuk melihat perbedaan domain health promoting lifestyle profile-2 (HPLP-II) antar kategori %LT pada mahasiswa Fakultas Kedokteran. Penelitian ini menggunakan metode kuantitatif observasional analitik dengan pendekatan cross-sectional. Subjek penelitian ini berjumlah 96 orang yang merupakan mahasiswa aktif Fakultas Kedokteran, bersedia melakukan pengukuran %LT, dan bersedia mengisi kuesioner sebagai kriteria inklusi. Kriteria eksklusi penelitian ini meliputi kuesioner tidak diisi dengan lengkap dan memiliki riwayat penyakit kongenital. Teknik pengambilan sampel menggunakan teknik purposive sampling. Persentase lemak tubuh diukur dengan metode bioimpedance analysis dan dikategorikan menjadi rendah, normal, overweight, dan obesitas. Domain profil gaya hidup promosi kesehatan dinilai dengan menggunakan kuesioner HPLP-II yang mencakup domain Health Responsibility (HR), Physical Activity (PA), Nutrition (N), Spiritual Growth (SG), Interpersonal Relationship (IR), dan Stress Management (SM). Hasil dari penelitian dianalisis dengan menggunakan one-way ANOVA. Hasil dari penelitian ini menunjukkan tidak adanya perbedaan yang signifikan antar kategori %LT pada semua domain HPLP: HR (p=0,964), PA (p=0,532), N (p=0,616), SG (p=0,547), IR (p=0,547), dan SM (p=0,376). Perbedaan yang tidak signifikan pada penelitian ini mungkin terjadi karena banyak faktor lain yang mempengaruhi %LT seperti genetik, metabolisme, dan budaya.